The characteristics and predictors of performance in trap shooting tournaments - Dwyer, D. B.; Sanders, N. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: To describe the characteristics of the performance of athletes in elite trap shooting tournaments and to identify factors that are associated with successful outcomes (i.e. qualification for finals and winning a medal). In addition, we sought to determine whether these characteristics differed over time and between tournaments. Methods: A database was compiled that describes the shot by shot outcomes of 2868 male and 1530 female performances, from 36 tournaments (Olympic, World Cup & World Championships) between 2011 and 2016. Descriptive statistics were used to represent the typical scores and ranking of athletes and non-parametric tests were used to make comparisons. Results: The qualifying score required to contest the finals did not change between 2011 and 2016 for males (120 ±2, p=0.08) or females (69 ± 2, p=0.12), nor is it different between tournament types (p=0.30). The strength of the relationship between each qualifying round score and the final qualifying score, qualitatively increases from the early to late rounds (r = 0.72 increasing to 0.83). There is no relationship between the qualifying score of finalists and their final tournament rank (r = 0.22-0.24), however a 1st-3rd qualifier has a 60% chance of being a medalist compared to 40% for a 4th to 6th qualifier. Conclusions: The characteristics of the qualifying performances of finalists has been relatively stable in the period of 2011 - 2016 and they did not vary between tournament types. Trap shooters must achieve a qualification score of 122 ± 1 (males) or 71 ± 2 (females) to be ranked in the top 3 qualifiers, to obtain a better than average likelihood of winning a medal.